2021
DOI: 10.1101/2021.06.02.21257975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Function is more reliable than quantity to follow up the humoral response to the Receptor Binding Domain of SARS-CoV-2 Spike protein after natural infection or COVID-19 vaccination

Abstract: On this work we report that despite of a decline in the total anti-Spike antibodies the neutralizing antibodies remains at a similar level for an average of 98 days in a longitudinal cohort of 59 Hispanic/Latino exposed to SARS-CoV-2. We are also reporting that the percentage of neutralization correlates with the IgG titers and that in the first collected samples, IgG1 was the predominant isotype (62.71%), followed by IgG4 (15.25%), IgG3 (13.56%), and IgG2 (8.47%) during the tested period. The IgA was detectab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…A previous study found that RBD-IgG persisted in 96.8% (31 of 32) of subjects at 14 months (21), which was slightly higher than 89.31% (284/318) at 15.6 months after symptom onset in our study. We also found that vaccinated individuals had higher antibody levels of IgG, RBD-IgG, S-IgG, N-IgG and neutralizing antibodies than unvaccinated individuals, consistent with the conclusions reached by Carlos et al (22).…”
Section: Discussionsupporting
confidence: 92%
“…A previous study found that RBD-IgG persisted in 96.8% (31 of 32) of subjects at 14 months (21), which was slightly higher than 89.31% (284/318) at 15.6 months after symptom onset in our study. We also found that vaccinated individuals had higher antibody levels of IgG, RBD-IgG, S-IgG, N-IgG and neutralizing antibodies than unvaccinated individuals, consistent with the conclusions reached by Carlos et al (22).…”
Section: Discussionsupporting
confidence: 92%
“…Pokazuje jednak, że metody oceny, kto jest ozdrowieńcem albo u kogo miano przeciwciał chroni przed chorobą, mają wady. Liczy się funkcja tych przeciwciał, a nie tylko ich stężenie [7]; podobnie jak liczba nawet uśpionych producentów przeciwciał (limfocytów B, które ich tymczasowo nie uwalniają), ich repertuar i zdolność do szybkiej reakcji -mobilizacji. Takiej oceny nie daje się dokonać w czasie testów przesiewowych powszechnie stosowanych do wykrycia przeciwciał.…”
Section: Skuteczność Szczepień W Warunkach Laboratoryjnychunclassified
“…The overall kinetics of the antibody response to SARS-CoV-2 is similar to that of SARS-CoV-1, characterized by expressed seroconversion (IgM / IgG) 7-14 days after the onset of symptoms and antibody concentrations persisting weeks to tens of months after infection (Henry et al 2020), A prospective study evaluating the kinetics of glycoprotein-specific antibodies in patients with COV-ID-19 found that IgA antibodies were produced early (in the first week) and peak at day 20-22, while IgM antibodies reached high titers at 10-12 th day, which subsequently decreases, usually 18 days after the onset of symptom (Sariol et al 2021). Our results show that at the end of the third month after illness, IgM titers tend to zero.…”
Section: Introductionmentioning
confidence: 99%
“…The aim was to evaluate the response of human antibodies to SARS-CoV-2 in 149 individuals recovering from COV-ID-19 of varying severity. Plasma neutralization of SARS-CoV-2 pseudovirus by convalescent patients with COV-ID-19 infection collected on average 39 days after the onset of symptoms has variable half-maximal neutralizing titers (NT50) (Sariol et al 2021). It should be noted that these are conclusions made on the basis of analysis of results obtained from in vitro laboratory methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation